Характеристика «соціального престижу» в контексті еволюційних змін. - Підгірна, Валентина Никифорівна; Філіпчук, Наталія (ЧНУ імені Юрія Федьковича, 2018)
The thesis analyzes the essence of the category of "social prestige" in the context of social inequality, reveals the synergy of social and professional prestige, justified the straight and direct interconnection of the prosperity of the population and social prestige.
Keywords: соціальний престиж; соціальна відповідальність; фінансова стабільність; прожитковий мінімум